Heterogeneity and Development of Fine Astrocyte Morphology Captured by Diffraction-Limited Microscopy - Minge, Daniel; Domingos, Cátia; Unichenko, Petr; Behringer, Charlotte; Pauletti, Alberto; Anders, Stefanie; Herde, Michel K.; Delekate, Andrea; Gulakova, Polina; Schoch, Susanne; Petzold, Gabor C.; Henneberger, Christian (Frontiers in Cellular Neuroscience, 2021)
The fine processes of single astrocytes can contact many thousands of synapses, whose function they can modulate through bi-directional signalling. The spatial arrangement of astrocytic processes and neuronal structures is relevant for such interactions and for the support of neuronal signalling by astrocytes. At the same time, the geometry of perisynaptic astrocyte processes is variable and dynamically regulated. Studying these fine astrocyte processes represents a technical challenge, because many of them cannot be fully resolved by diffraction-limited microscopy. Therefore, we have established two indirect measures of astrocyte morphology: the fraction of tissue volume that astrocytes occupy and the density of resolvable astrocytic processes. Both are straight-forward to obtain using widely available microscopy techniques. We here present and verify the approach. In addition, we demonstrate its robustness across various experimental conditions using mainly two-photon excitation fluorescence microscopy in acute slices and in vivo as well as modelling. Using these indirect measures allowed us to analyse the fine morphology of relatively large populations of astrocytes. Doing so we captured the heterogeneity of astrocytes within and between the layers of the hippocampal CA1 region and the developmental profile of astrocyte morphology. This demonstrates that volume fraction and segment density are useful parameters for describing fine astrocyte morphology. They are also suitable for on-line monitoring of fine astrocyte morphology with widely available microscopy techniques.